THE SECRET TO EXCLUSIVE BREASTFEEDING SUCCESS AT TPMB SITI NURUSSAKINATURAHMAH SERANG 2024 - Marthia Ikhlasiah; Ana Marliana; Refi Lindawati (ZILLZELL MEDIA PRIMA, 2025)
This study aims to find out the factors that affect the success of breastfeeding in newborns. This type of research is using Qualitative with Cross Sectional design, in the design of data collection using primary data, namely with an observation sheet carried out on one group without a control group or comparator. The sample of this study is mothers who give birth at TPMB Siti Nurussakinaturrahmah. S.Keb. In Serang City in 2024, a total of 30 respondents were taken by accidental sampling from September – November 2024. The statistical analysis used is the Chi-Square Test. Based on the results of the statistical test using chi square, it was shown that there was a meaningful relationship between the support of the husband and the support of health workers with the incidence of successful breastfeeding in newborns with a p-value of <0.05, while there was no meaningful relationship between knowledge and the success of breastfeeding in newborns with p-value 0.05. The conclusion of this study is that mothers who have good knowledge will give breast milk to their babies, and mothers who have newborns are expected to receive support from their husbands and health workers. Saran Diis is expected to be able to conduct further research elsewhere, with a larger number of samples, as well as with different research designs such as the case control design.